Translation as Writing Across Languages: Samuel Beckett and Fakir Mohan Senapati - St-Pierre, Paul (TTR, 1996)
AbstractTranslation as Writing Across Languages: Samuel Beckett and Fakir Mohan Senapati — This paper attempts to demonstrate that translation cannot be divorced from writing, that originality and creativity are not characteristic only of the latter, that translation is not mere reproduction. This is developed in relation to Samuel Beckett's translations of his own works and five translations of a passage of a late nineteenth-century Indian novel. In the case of Samuel Beckett, translation is seen as a way both to begin and to continue the writing process, a way for him to explore one of the principal themes of his work, the relation of writing to language(s). In that of the five translations into English of a passage from the Oriya novel by Fakir Mohan Senapati, Chha Mana Atha Guntha, the differences between them are examined for the purpose of showing the extent to which the practice of translation is always an act of creative writing.